Development of Interactive Multimedia Mobile Learning in Biology Learning at MAN 2 Tuban - Khotimah, Inggreet Ayu Khusnul; Adi, Eka Pramono; Husna, Arafah (Proceedings Series of Educational Studies, 2024)
This development was motivated by the problem that class X MIPA at MAN 2 Tuban had not maximized the use of technology, causing a decrease in student motivation when studying. Student learning motivation is important because it can be a trigger in increasing the completeness of student learning outcomes in class. So the aim of this research and development is to produce interactive mobile learning multimedia that is valid and feasible, especially in learning biology, ecosystem component elements and their interactions. This development involves stages of analysis, design, development, implementation and evaluation following the ADDIE framework. The resulting product has gone through a validation process by media experts and material experts. Testing was carried out on class X MIPA students at MAN 2 Tuban. The results of this development show a high level of validity, with the match percentage from media experts reaching 100%, material experts reaching 97.3%, individual trials reaching 82%, small group trials reaching 93%, and large group trials reaching 89%. Apart from that, interactive multimedia mobile learning can increase the completeness of student learning outcomes so that it can be used in classroom learning activities because it reaches a percentage of 89.64% and is a valid and appropriate qualification. Keywords: Interactive Multimedia, Mobile Learning, Biology